The effect of temperature changes on to quasi-static tensile and flexural performance of glass fibre reinforced PA66 composites - Butterworth, Ian; Abhyankar, Hrushikesh; Westwood, Keith; Njuguna, James; Brighton, James; Mouti, Zakaria (Cranfield University Press, 2013)
A significant method of reducing CO2 emissions in road vehicles is to reduce the vehicle mass. One means in which this can be achieved is to adopt lightweight materials such as thermoplastic composites. Thermoplastics offer advantages in term of weight when compared to conventional steel and aluminium casting. In this study thermal mechanical testing has been conducted on two types of commercial polyamide 66 (PA66) with 35 wt.% short glass fibre reinforcement. One of the materials was impact modified with an elastomer to increase material toughness. Experimental results showed both the reinforced PA66 materials to be temperature dependent. All test results demonstrated the trade-off in the mechanical properties of the two materials especially the impact modified. PA66 with 35 wt.% short glass fibre exhibits the best tensile strength, flexural strength and modulus for each temperature tested. Whereas the impact modified PA66 with 35 wt.% short glass fibre exhibits the higher strain and toughness for each temperature tested.
Keywords: Thermoplastic; Polyamide 66; Short Glass Fibre Reinforced